2010
DOI: 10.7202/038875ar
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Racial Differentials in Promotions

Abstract: Summary Using a proprietary dataset containing personnel records on over 22,000 full-time, non-unionized employees from a large Canadian firm with nationwide operations from 1996 to 2000, this paper explores the incidence of promotion for women and racial minorities. The findings show that women and racial minorities are less likely than their white male counterparts to be promoted. For both white women and minority women, the disadvantage is most severe at the lower rungs of the organizational hiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(28 citation statements)
references
References 71 publications
2
18
0
Order By: Relevance
“…Overall, our findings contribute to the literature on the existence and drivers of a gender gap in the workplace, and specifically at the top of the organizational hierarchy. Going forward, efforts to understand differences in career advancement should examine both speed of advancement and promotion rates (e.g., Gorman & Kmec, 2009;Jones & Makepeace, 1996;Smith, Smith, & Verner, 2013;Yap & Konrad, 2009;Zeng, 2011). Our results also contribute to the literature that studied the effectiveness and limits of institutional pressures in reducing gender inequality in the workplace (Dezső et al, 2016;Dobbin & Kalev, 2017;Gregorič, Oxelheim, Randøy, & Thomsen, 2017).…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…Overall, our findings contribute to the literature on the existence and drivers of a gender gap in the workplace, and specifically at the top of the organizational hierarchy. Going forward, efforts to understand differences in career advancement should examine both speed of advancement and promotion rates (e.g., Gorman & Kmec, 2009;Jones & Makepeace, 1996;Smith, Smith, & Verner, 2013;Yap & Konrad, 2009;Zeng, 2011). Our results also contribute to the literature that studied the effectiveness and limits of institutional pressures in reducing gender inequality in the workplace (Dezső et al, 2016;Dobbin & Kalev, 2017;Gregorič, Oxelheim, Randøy, & Thomsen, 2017).…”
mentioning
confidence: 66%
“…The alternative explanation for our finding that women executives got to the executive suite faster is unobserved ability, specifically that the women were more qualified in ways that our observed education and career experience characteristics could not capture. Discrimination at lower levels might produce a smaller pool of female candidates who were nevertheless more motivated and ultimately more qualified than the men (Ferree & Purkayastha, 2000;Yap & Konrad, 2009), attributes that would propel them faster to the top of the corporate hierarchy.…”
Section: Alternative Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vertical segregation means limiting promotion and career opportunities. Many studies have shown that women are less likely to be promoted than their male colleagues who have the same qualifications (Blau & Devaro 2007, Hau Siu Chow & Crawford 2004, Lyness & Heilman 2006, Yap & Konrad 2009. Women also constitute only a small percentage of CEOs in most countries that belong to the Organisation for Economic Cooperation and Development (OECD), despite the fact that they are as well educated as men and have actively participated in the labour market for several decades (Manpower 2008).…”
Section: Introductionmentioning
confidence: 99%